Analisis Kelayakan Usaha Ternak Kambing Pada Kelompok Usaha Bersama (KUB) Mondroguno - Hana Nur Eritrina (Manajemen Agribisnis: Jurnal Agribisnis, 2022)
This research was conducted on goat farming at KUB Mondroguno, Desa Rowomarto, Kecamatan Patianrowo, Kabupaten Nganjuk. The purpuse of this research is to conduct a business feasibility analysis on the goat business of KUB Mondroguno. The research method chosen is descriptive with case studies. The analysis conduct by analyzing technical aspects, social environtment and socio-cultural aspects, financial aspects, juridical aspects, and marekting aspects. Based on the feasibility analysis of technical aspects, the business running well . Apects of human resources who become business managers are also sufficience to run this micro-scale business. Environmentally and socio-culturally, this business can provide example of entreprneurial practices to the comunity. Goat dung can be used as organic fertilizer and compost for agriculture. The succes of the business is supported by juridical and legal aspects that have been fulfiled by KUB Mondroguno. Based on calculation of R/C ratio the business is feasible shown by R/C = 1,351 above the criteria. Marketing aspects analysis of KUB Mondorguno was conducted by mapping the marekt to be two category. The firs is business such as restaurant, catering, and other agency that need goat meet as the ingredient for his menu. By analyzing these five aspects, it can be infered that goat farming business by KUB Mondroguno is feasible.